2022
DOI: 10.1155/2022/5300523
|View full text |Cite
|
Sign up to set email alerts
|

On the Core Prescriptions and Their Mechanisms of Traditional Chinese Medicine in Hepatitis B, Liver Cirrhosis, and Liver Cancer Treatment

Abstract: Background. As a frequent cause of death in cancer patients, liver cancer usually occurs in hepatitis B and cirrhosis. In China, Chinese people have been using traditional Chinese medicine (TCM) in treating various chronic liver diseases, which could effectively improve the symptoms and slow down the progression of liver diseases. However, due to the complexity rules of TCM prescription, their action mechanisms are still not clearly understood, which may affect the popularization of effective prescriptions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Research indicates that traditional chinese medicine offers significant treatment for most types of cancers including lung cancer, 17 liver cancer, 18 stomach cancer, 19 breast cancer, 20 esophageal cancer, 21 colorectal cancer, 15 and nasopharyngeal (throat and sinus) cancer 22 . Cancer patients mostly are given traditional Chinese medicine and conventional medical treatments 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that traditional chinese medicine offers significant treatment for most types of cancers including lung cancer, 17 liver cancer, 18 stomach cancer, 19 breast cancer, 20 esophageal cancer, 21 colorectal cancer, 15 and nasopharyngeal (throat and sinus) cancer 22 . Cancer patients mostly are given traditional Chinese medicine and conventional medical treatments 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It also has a high frequency of use in the prevention and treatment of tumors [24]. With the in-depth development of chemical technology, there have been many reports on the pharmacological effects and mechanisms of PRA and its active ingredients, confirming that it has a wide range of pharmacological effects, including analgesic [25], anti-inflammatory [26], antidepressant [27,28], hepatoprotective [29], immune modulation [30] and significant antitumor activity, and it plays a therapeutic role in gastric cancer, hepatocellular carcinoma, pancreatic cancer and other malignant tumors [31,32]. This paper mainly introduces the main active ingredients of PRA and summarizes the mechanism of action of PRA and its active ingredients in the treatment of various malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there are no specific effective drugs available for liver fibrosis treatment in the clinical setting. Accumulating evidences have demonstrated that Chinese herbal medicine has good preventive and therapeutic effects in various liver diseases, such as liver injury [ 4 ], liver fibrosis [ 5 ], hepatitis and cirrhosis [ 6 ], and has some unique advantages including high availability, multiple targets and few side effects.…”
Section: Introductionmentioning
confidence: 99%